Combined Experimental and Computational Investigation of the Fluorescence Quenching of Riboflavin by Cinnamic Alcohol Chemisorbed on Silica Nanoparticles - Arce, Valeria Beatriz (2014)
Riboflavin (vitamin B2) is usually present in water courses, lakes, and seas and acts as a photosensitizer in the photo-oxidation of a range of contaminants. However, little is known about the interaction of this compound with aromatics sorbed on silica sediments or on suspended silica particles. This article describes the modification and characterization of silica nanoparticles by condensation of the silanol groups of the particles with E-cinnamic alcohol. The reaction was confirmed by Fourier transform infrared spectroscopy (FTIR), solid-state 13C and 29Si crosspolarization magic angle spinning (CPMAS) NMR, reduction of the specific surface area measured by BET, thermal analysis, and fluorescence spectroscopy. Toxicity to the marine bacteria Vibrio fischeri of the modified particles was also measured. Riboflavin fluorescence was quenched in aqueous medium in the presence of dissolved E-cinnamic alcohol or in suspensions of the modified particles. The results are interpreted in terms of formation of 1:1 complexes between the ground states of riboflavin and the free or adsorbed cinnamic alcohol. Density functional theory (DFT) calculations in aqueous medium support the existence of the complex and explain the observed quenching of riboflavin fluorescence upon addition of cinnamic alcohol without affecting the emission maximum of riboflavin.